2018
DOI: 10.1093/scipol/scy028
|View full text |Cite
|
Sign up to set email alerts
|

Innovation intermediaries and performance-based incentives: A case study of regional innovation poles

Abstract: A growing number of innovation policies rely on publicly funded innovation intermediaries to provide knowledge-intensive services to firms, particularly small and medium-sized ones. The performance of innovation intermediaries is often assessed using indicators that need to be closely aligned with policy objectives to be effective. However, this alignment is difficult to achieve and is often overlooked in practice. We analyse the relationship between performance indicators and the behaviour of intermediaries b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…In addition to facilitating the interplay between co-localised universities and firms, intermediaries may help convey flows of external knowledge into the local context (Breschi & Lenzi, 2015;Calignano, 2019;Giuliani, 2011;Hazır, LeSage, & Autant-Bernard, 2018). Intermediaries can play an important role in the regional innovation process: they can facilitate the exchange among agents who differ in their background knowledge, competencies, decision-making horizons, incentives, objectives, as well as in their location (Bessant & Rush, 1995;Cantner et al, 2011;Knockaert, Spithoven, & Clarysse, 2014;Russo, Caloffi, Rossi, & Righi, 2018). Therefore, they are expected to add some value to the collaboration between consortium partners belonging to different institutional spheres (McEvily & Zaheer, 1999).…”
Section: Incoming Spillovers and Absorptive Capacitymentioning
confidence: 99%
“…In addition to facilitating the interplay between co-localised universities and firms, intermediaries may help convey flows of external knowledge into the local context (Breschi & Lenzi, 2015;Calignano, 2019;Giuliani, 2011;Hazır, LeSage, & Autant-Bernard, 2018). Intermediaries can play an important role in the regional innovation process: they can facilitate the exchange among agents who differ in their background knowledge, competencies, decision-making horizons, incentives, objectives, as well as in their location (Bessant & Rush, 1995;Cantner et al, 2011;Knockaert, Spithoven, & Clarysse, 2014;Russo, Caloffi, Rossi, & Righi, 2018). Therefore, they are expected to add some value to the collaboration between consortium partners belonging to different institutional spheres (McEvily & Zaheer, 1999).…”
Section: Incoming Spillovers and Absorptive Capacitymentioning
confidence: 99%
“…By collecting, selecting, scanning, coding and sharing knowledge, government-supported intermediaries with moral legitimacy reduce cognitive and organisational distances and information asymmetry among collaborators (Cho et al, 2016;Kivimaa, 2014;Lin et al, 2018;O'kane et al, 2015;Villani et al, 2017). Training, supportive services, meetings, face-to-face communication and other means are important sources of information gathering and diffusion for intermediaries to play a role in improving the performance of innovative collaborators (Russo et al, 2018). Intermediaries are important infrastructures that constitute regional absorptive capacity, and they can minimise opportunistic behaviour and enhance the absorptive capacity of collaborators (Qiu et al, 2017).…”
Section: Moderation Effects Of Intermediariesmentioning
confidence: 99%
“…These institutional settings often play a transformative role in framing the conditions for knowledge transfer between industry and science. Intermediary organisations differ in their size, mission, activities, ownership, and funding structure (Russo et al, 2018). Some are autonomous agencies tasked with promoting knowledge transfer and innovation more generally while others are established as units of a specific university, as is often the case of TTOs and science parks.…”
Section: Multi-level Governance Of the Policy MIXmentioning
confidence: 99%
“…Policy makers' choice of performance indicators to evaluate intermediary organisations (such as number of spin-offs, patent licencing contracts, research contracts, or joint research projects) can lead to undesirable effects if performance indicators are not well aligned with policy objectives or if indicators focus only on a few channels of knowledge transfer just because they are easier to measure (Russo et al, 2018). For example, Gulbrandsen and Rasmussen (2012) found that using the number of spin-offs as a performance indicator for technology transfer offices in Norway led to the adverse effect of pushing them to launch as many firms and as fast as possible, even if their survival chances were low.…”
Section: Negative Interactionsmentioning
confidence: 99%